Perspektif Hukum Ekonomi Syari'ah Terhadap Jual Beli Pada Tempat yang Dilarang - Sohibul Hizbullah; Basri Na’ali (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The rise of street vendors (PKL) who practice buying and selling in places prohibited by the Bukittinggi City government. The Regional Regulation of the City of Bukittinggi Number 8 of 2014 Concerning the Arrangement and Empowerment of Street Vendors, stipulated on April 14 2014, contains provisions for buying and selling for street vendors. Based on these provisions stipulates that the Jam Gadang tourist park is a place where buying and selling is prohibited. Even though there are regulations governing it, there are still many street vendors (PKL) who commit violations. This practice is something that needs to be researched about how the perspective of Islamic economic law is on the status of the sale and purchase contract carried out by the street vendors (PKL). This study focuses on the legal perspective of sharia economics on the status of buying and selling contracts carried out by street vendors in prohibited places. This type of research is field research using data collection methods, namely interviews, observation and literature. The research approach used is juridical and normative, namely by using the rules of fiqh and positive law related to the problem under study. The results of the study state that the status of the sale and purchase contract carried out by street vendors (PKL) in the Jam Gadang park area is harmonious and the terms of sale and purchase are in sharia economic law, but in practice it often causes problems and ignores the general benefit that should be embodied in regulations. the area.